Strategies for development and implementation of bio-based materials as effective renewable resources of energy: A comprehensive review on adsorbent technology. (September 2016) - Ummartyotin, S.; Pechyen, C.
Abstract: The use of bio-based waste gained many interests exponentially for supporting on the use of non-toxic materials. During the last three decades, bio-based waste in form of bio-based polymer and bio-based ceramic such as cellulose, chitin-chitosan, porous clay, eggshell, activated carbon and so on have been extensively designed for being as sorbent material. The use of bio-based waste was encourages due to low cost of materials and availability of product. Moreover, due to sustainable concept on the use of bio-based waste, numerous innovative processes have been extensively employed to modify on surface and structure in order to tailor the excellent performance as sorbent material. The example of process was due to chemical treatment and physical modification. Additional information on bio-based sorbent material will provide significant idea on energy policy in future. In this review article, the objective was to present on the overview on bio-based waste and its modification technique and the potential application as sorbent material for energy policy will be discussed.